TANGGUNG JAWAB NEGARA PELUNCUR ATAS KERUGIAN YANG DITIMBULKAN BENDA ANTARIKSA BERDASARKAN LIABILITY CONVENTION 1972 - Waode Zessica Harta Setiati Agus Pramono, Soekotjo Hardiwinoto (Diponegoro Law Journal, 2012)
The growing commercialization of outer space today has led us to a new era of space activities. Indicator of this is the increasing number of space objects which are placed the room in space. Above it is the possibility of loss or negative impact from a space object will also be greater. Therefore we need an international legal arrangements governing the legal issues space, one of that space law is the Liability Convention 1972 about governing state liability for any loss or damage launcher that caused the space object.